RELIGIOUS MODERATION AND TRANSFORMATION: GUS IQDAM IN STRENGTHENING TOLERANCE AND PEACE AMONG DIVERSE YOUTH - Siswoyo Aris Munandar (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Gus Iqdam is one of the most influential young religious figures among Indonesian youth, particularly through his active engagement on social media platforms. His contextual and communicative preaching style has drawn widespread attention and made him a frequently invited speaker at public and religious forums. This study aims to examine the role and preaching strategies of Gus Iqdam in disseminating inclusive and adaptive Islamic messages in the digital era. The main focus is on how he creatively uses social media and communication strategies to engage younger audiences, including those who have previously been distant from religious practices. Using a netnographic and phenomenological approach, this research explores how Gus Iqdam successfully builds rapport with groups that are often overlooked by conventional religious outreach, such as individuals with prior experiences of socially deviant behavior or those from non-Muslim backgrounds. The findings indicate that his success lies in his ability to convey religious values empathetically and in ways that resonate with the lived realities of contemporary youth. This study contributes to a deeper understanding of effective media-based da'wah strategies in a pluralistic, digital society, enriching the discourse on culturally and inclusively oriented Islamic preaching in Indonesia.